Preparation, cytotoxic activity and DNA interaction studies of new platinum(II) complexes with 1,10-phenanthroline and 5-alkyl-1,3,4-oxadiazol-2(3H)-thione derivatives - Souza, Wesley A.; Ramos, Luana M.S.; de Almeida, Angelina M.; Tezuka, Daiane Y.; Lopes, Carla D.; Moreira, Mariete B. [UNESP]; Zanetti, Renan D. [UNESP]; Netto, Adelino V.G. [UNESP]; Ferreira, Francis B.; de Oliveira, Ronaldo Junio; Guedes, Guilherme P.; de Albuquerque, Sérgio; et al. (Elsevier, 2022)
This work describes the synthesis, characterization and in vitro anticancer activity of two platinum(II) complexes of the type [Pt(L1)2(1,10-phen)] 1 and [Pt(L2)2(1,10-phen)] 2, where L1 = 5-heptyl-1,3,4-oxadiazole-2-(3H)-thione, L2 = 5-nonyl-1,3,4-oxadiazole-2-(3H)-thione and 1,10-phen = 1,10-phenanthroline. As to the structure of these complexes, the X-ray structural analysis of 1 indicates that the geometry around the platinum(II) ion is distorted square-planar, where two 5-alkyl-1,3,4-oxadiazol-2-thione derivatives coordinate a platinum(II) ion through the sulfur atom. A chelating bidentate phenanthroline molecule completes the coordination sphere. We tested these complexes in two breast cancer cell lines, namely, MCF-7 (a hormone responsive cancer cell) and MDA-MB-231 (triple negative breast cancer cell). In both cells, the most lipophilic platinum compound, complex 2, was more active than cisplatin, one of the most widely used anticancer drugs nowadays. DNA binding studies indicated that such complexes are able to bind to ct-DNA with Kb values of 104 M−1. According to data from dichroism circular and fluorescence spectroscopy, these complexes appear to bind to the DNA in a non-intercalative, probably via minor groove. Molecular docking followed by semiempirical simulations indicated that these complexes showed favorable interactions with the minor groove of the double helix of ct-DNA in an A-T rich region. Thereafter, flow cytometry analysis showed that complex 2 induced apoptosis and necrosis in MCF-7 cells.
Keywords: Apoptosis; Cytotoxic activity; DNA binding; Molecular docking; Necrosis; Platinum(II) complexes